2023
DOI: 10.5851/kosfa.2022.e75
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Starter Cultures on Quality of Fermented Sausages

Abstract: Ethics approval (IRB/IACUC) (This field may be published.) This article does not require IRB/IACUC approval because there are no human and animal participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The S1 and S2 sucuk groups had higher hardness values on the last day of storage (p<0.05). It has been reported that the decrease in pH and water activity due to microbial activity during ripening process give final sucuk product its unique texture and consistency that makes it easy to slice (Hwang et al, 2023). In terms of adhesiveness values, a significant difference was determined between the sucuk groups on all days of the storage (p<0.05).…”
Section: Texture Resultsmentioning
confidence: 92%
“…The S1 and S2 sucuk groups had higher hardness values on the last day of storage (p<0.05). It has been reported that the decrease in pH and water activity due to microbial activity during ripening process give final sucuk product its unique texture and consistency that makes it easy to slice (Hwang et al, 2023). In terms of adhesiveness values, a significant difference was determined between the sucuk groups on all days of the storage (p<0.05).…”
Section: Texture Resultsmentioning
confidence: 92%
“…However, the external color of the SM salami showed a higher (p > 0.05) yellowish (b*) value than SR, likely affected by the homogeneous growth of molds on the entire external surface [46]. SR exhibited a higher (p > 0.05) redness (a*) value than SM, probably due to the presence of Staphylococcus carnosus in the starter cultures, which helps maintain the red color [47]. The hue angle value was significantly affected (p < 0.05) by the use of a different starter culture, showing a significantly (p < 0.01) higher value in the external surface of SR than SM.…”
Section: Rheological and Colorimetric Resultsmentioning
confidence: 97%
“…The comparison of B1B3D24 and B2B3 in Figure C shows a superactive positive pathway in FA(22:0) to FA(24:0); FA(16:1) to FA(18:1) and to FA(18:2); and FA(18:3) to FA(20:3). A study also shows that the presence of essential fatty acids including oleic acid, linoleic acid, γ-linolenic acid, and isotopomers of ω3 and ω6 fatty acids increased as a result of starter cultures of LAB, which enhances lipid hydrolysis and metabolism. , …”
Section: Resultsmentioning
confidence: 97%
“…The increase and decrease of TTA are mainly related to the change in lactic acid production and protein hydrolysis, and the same result was also seen in Hwang et al ( 2010), indicating that the main reason behind this can be related to the production of lactic acid and the presence of free amine group. 38,39 The highest TTA was observed in B1B3D24 followed by B2B3D24 and B2B3 sausage samples at 25 days of fermentation. The increase in TTA is associated with the glucose pathway in the synthesis of lactic acid during the fermentation stage.…”
Section: Lipid Mediator Genes Comparison and Correlationmentioning
confidence: 96%
See 1 more Smart Citation